2021
DOI: 10.3390/polym13172890
|View full text |Cite
|
Sign up to set email alerts
|

α-Mangostin/γ-Cyclodextrin Inclusion Complex: Formation and Thermodynamic Study

Abstract: α-Mangostin (α-M) has various biological activities, such as anti-cancer, antibacterial, anti-fungal, anti-tyrosin, anti-tuberculosis, anti-inflammatory, and antioxidant. However, it has very low solubility in water. The formulation of this compound requires high amounts of solubilizers, which limits its clinical application. In addition, its low solubility in water is a barrier to the distribution of this drug, thus affecting its potency. Cyclodextrin (CD) is widely used as a solubility enhancer of poorly sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, the potential of α-mangostin tends to be hindered due to its unfavorable physicochemical properties. Its low solubility in water makes it difficult to formulate into drug preparations, especially for oral administration, which is commonly preferred by patients [ 28 , 29 ]. Interestingly, the potential of other isolated xanthone derivative compounds from the pericarp of Garcinia mangostana L. has not been further explored for their potency in combating SARS-CoV-2 and their compatibility to be formulated as oral drug preparations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential of α-mangostin tends to be hindered due to its unfavorable physicochemical properties. Its low solubility in water makes it difficult to formulate into drug preparations, especially for oral administration, which is commonly preferred by patients [ 28 , 29 ]. Interestingly, the potential of other isolated xanthone derivative compounds from the pericarp of Garcinia mangostana L. has not been further explored for their potency in combating SARS-CoV-2 and their compatibility to be formulated as oral drug preparations.…”
Section: Introductionmentioning
confidence: 99%
“…The molecule, included in the complex, is protected by the macromolecule against a harmful influence of varied external factors such as high temperature or UV radiation [ 20 , 21 ]. Cyclodextrins can be successfully used in complexing medicines [ 22 , 23 ] and other biologically active compounds [ 24 ]. Song et al showed that cyclodextrins can also be used to remove organic micropollutants from water [ 25 ].…”
Section: Introductionmentioning
confidence: 99%